Synthesis of Gold Dendrites in a Green Chemistry Approach Using Hydroxyethyl Cellulose - Jahir Hussain, Fathima Shahitha; M. M., Yusoff (2011)
In this work we report a simple method of preparation of gold dendrites using hydroxyethyl cellulose (HEC) in a green chemistry approach using only water as the solvent. Here HAuCl4 is reduced to nanodendrites using HEC, which acts as a reducing as well as stabilizing agent. Depending on the reaction conditions gold nanoparticles, snake shaped gold nanostructures and gold dendrites were formed. The gold nanostructures were characterized using transmission electron microscopy. These gold nanostructures are biocompatible and biodegradable.